Ações afirmativas para negros no Brasil: o início de uma reparação histórica - Petrônio Domingues (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2005)
The propose of this article is to exami-ne affirmative actions which benefit the black population, taking as it sargument the controversy about the institution of a programme of racialquotas, especially in public universities. It concludes that such aprogramme represents a landmark inthe countrys history: on the one hand,because it is the first time that theBrazilian state seeks to make amendsfor past (and present) injustices to theblack population and, on the other,because it also represents the first timethat public national opinion has beenso involved in the problem of anti-black racism and in discussingpossible solutions.